Clinico-biochemical correlation between psoriasis and lipid profile - Gupta, Amita; Paneri, Sangita; Lohokare, Rajeev; Sarkar, P. Dey; Jain, Anil (International Journal of Research in Medical Sciences, 2017)
Background: Psoriasis is an autoimmune disorder associated with alteration of different metabolism. The present study was aimed to assess the lipid metabolism and its correlation with severity of disease and associated cardiovascular risk factors in psoriasis. Methods: Study comprises total of 60 cases of psoriasis attended the dermatology clinics at Maharaja Yashwant Rao hospital, Indore, Madhya Pradesh, India and 30 age, gender matched healthy controls. Subjects were enrolled in the study as per the inclusion criteria. Severity of the disease was assessed by PASI score. Fasting blood samples were collected and evaluated for Lipid profile and risk ratio was calculated. Results: The results indicated that serum total cholesterol, triglycerides, LDL-C,VLDL-C were significantly increased in moderate to severe cases in comparison to control and level of HDL-C significantly decreased in moderate psoriasis and highly significant decreased was observed in severe cases when compared to control. Serum triglyceride (TG), total cholesterol, low density lipoprotein showed a significant positive correlation with severity of psoriasis. Study concludes that lipid derangement correlate with the severity of disease and also acts as a good prognostic sign. Conclusions: Present study concludes that psoriatic patients should be evaluated and followed up for the risk of dyslipidemia and cardiovascular morbidity.